(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we introduce the concept of square-mean pseudo S-asymptotically (ω,c)-periodic for stochastic processes and establish some composition and convolution theorems for such stochastic processes. In addition, we investigate the existence and uniqueness of square-mean pseudo S-asymptotically (ω,c)-periodic mild solutions to some stochastic fractional integrodifferential equations. We illustrate our main results with an application to stochastic Weyl fractional integrodifferential equations.